Comparison of Income Tax Calculations for Individual Taxpayers with PKP of More Than 5 Billion Based on Law Number 36 of 2008 and Law Number 7 of 2021 - Sugiarti, Alisa Dwi; Murti, Galuh Tresna; Nur Annisa, Agitha Naya; Rahmah, Cahya Fathya (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Makassar, 2023)
This study aims to compare and analyze the calculation of income tax for Individual Taxpayers (WPOP) who have Taxable Income (PKP) of more than IDR 5 billion before the HPP Law was enforced, namely based on Law No.36 of 2008 and after the HPP Law was enforced. The method used in this study is a qualitative descriptive method with data collection techniques using literature and then analyzed based on calculation analysis. The results of the study show that for individual taxpayers with PKP of more than IDR 5 billion, the tax burden paid is higher under the HPP Law compared to the PPh Law. The application of the HPP Law is in accordance with the principle of justice, namely that taxes are imposed according to the ability of the taxpayer. The higher the income, the higher the tax that must be paid.